One-pot green synthesis of 1, 3, 5-triarylpentane-1, 5-dione and triarylmethane derivatives as a new class of tyrosinase inhibitors. Issue 3 (1st February 2016) - Zheng, Zong-Ping; Zhang, Yi-Nan; Zhang, Shuang; Chen, Jie
Graphical abstract: Abstract: A new method was developed for one-pot green synthesis 1, 3, 5-triarylpentane-1, 5-dione, triarylmethane, and flavonoid derivatives from the reaction between 2, 4-dihydroxybenzaldehyde and hydroxyacetophenones via Aldol, Michael, and Friedel–Crafts additions using boric acid as catalyst in polyethylene glycol 400. The synthetic compounds demonstrated significant tyrosinase inhibitory activities much stronger than that of kojic acid. More important, 1, 3, 5-triarylpentane-1, 5-dione and triarylmethane derivatives were found to be a new class of tyrosinase inhibitors.